Genetic knockdown of DYRK1A attenuates cognitive impairment, Aβ pathology, tauopathy and neuroinflammatory responses in mouse models of AD - Lee, Hyun-ju; Kang, Sora; Lee, Yoo Jin; Oh, Seokjun; Joo, Bitna; Hwang, Jeong-Woo; Kim, Jeongseop; Kim, Tae-Eun; Jung, Tae-Mi; Kim, Yu-Jin; Jang, Ji-Yeong; Song, Jeong-Heon; et al. (Frontiers in Immunology, 2025)
IntroductionDual specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) is associated with the pathoprogression of neurodevelopmental and neurodegenerative disorders. However, the effects of direct genetic manipulation of DYRK1A in the brain on cognitive function, neuroinflammation and Alzheimer’s disease (AD) pathology and underlying molecular mechanisms have not been fully investigated.MethodsTo determine whether overexpressing or knocking down DYRK1A expression directly in the brain affects cognitive function, neuroinflammation and AD pathology, adeno-associated viruses (AAVs) were injected into the hippocampus of wild-type (WT), 5xFAD, and PS19 mice. Then, cognitive function was assessed via Y-maze and novel object recognition (NOR) tests, and neuroinflammatory responses and AD pathologies were analyzed by real-time PCR, Western blotting, immunofluorescence staining, AD-associated protein activity assays and ELISA.Results and discussionIn WT mice, hippocampal DYRK1A overexpression significantly reduced short-term spatial/recognition memory and SynGAP expression while increasing p-P38 levels. Conversely, in amyloid-beta (Aβ)-overexpressing 5xFAD mice, hippocampal DYRK1A knockdown improved short-term spatial/recognition memory and significantly increased CaMKIIα and CREB phosphorylation. Moreover, hippocampal DYRK1A knockdown in 5xFAD mice significantly suppressed mRNA levels of proinflammatory cytokines and markers of AD-associated reactive astrocytes (RAs), disease-associated microglia (DAMs), and RA–DAM interactions. However, hippocampal DYRK1A overexpression in 5xFAD mice increased mRNA levels of the proinflammatory cytokine IL-1β, RA markers and the microglial marker Iba-1. Interestingly, hippocampal DYRK1A knockdown in 5xFAD mice significantly increased levels of the anti-oxidative/inflammatory molecule HO-1 without altering p-STAT3/p-NF-κB levels. By contrast, hippocampal DYRK1A overexpression in 5xFAD mice enhanced STAT3/NF-κB phosphorylation but did not affect ROS levels. Importantly, hippocampal DYRK1A knockdown in 5xFAD mice significantly reduced Aβ plaque number, soluble Aβ40 levels, and soluble/insoluble Aβ42 levels by suppressing β-secretase BACE1 activity but not tau hyperphosphorylation. Finally, hippocampal DYRK1A knockdown in PS19 mice [a model of AD that overexpresses human mutant tau (P301S)] selectively decreased insoluble tau hyperphosphorylation at Ser396 and Ser404 and alleviated proinflammatory responses/glial-associated neuroinflammatory dynamics. Taken together, our data indicate that DYRK1A modulates cognitive function, neuroinflammation, and AD pathology (Aβ and tauopathy) in mouse models of AD and/or WT mice and support DYRK1A as a potential therapeutic target for AD.